Does Code Coverage Provide a Good Stopping Rule for Operational Profile Based Testing? - Miranda, Breno; Bertolino, Antonia (2016 IEEE/ACM 11th International Workshop in Automation of Software Test (AST), 2016)
We introduce a new coverage measure, called the operational coverage, which is customized to the usage profile (count spectrum) of the entities to be covered. Operational coverage is proposed as an adequacy criterion for operational profile based testing, i.e., to assess the thoroughness of a black box test suite derived from the operational profile. To validate the approach we study the correlation between operational coverage of branches, statements, and functions, and the probability that the next test input will not fail. On the three subjects considered, we observed a moderate correlation in all cases (except a low correlation for function coverage for one subject), and consistently better results than traditional coverage measure.